2017
DOI: 10.1074/jbc.m117.797100
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure–function characterization of a signaling-active rhodopsin–G protein complex

Abstract: The visual photo-transduction cascade is a prototypical G protein-coupled receptor (GPCR) signaling system, in which light-activated rhodopsin (Rho*) is the GPCR catalyzing the exchange of GDP for GTP on the heterotrimeric G protein transducin (G T ). This results in the dissociation of G T into its component ␣ T -GTP and ␤ 1 ␥ 1 subunit complex. Structural information for the Rho*-G T complex will be essential for understanding the molecular mechanism of visual photo-transduction. Moreover, it will shed light… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Notably, this study revealed the putative role of the Gb 1 and the a-helical domain (aHD) of the Ga subunit in the G protein activation process. Whereas aHD is highly flexible (107)(108)(109) and therefore it remains unresolved in other GPCR/G protein cryo-EM structures, Gao et al (108) solved the structures of three Rho/G T complex conformers (at 4.5 Å) that differed in degrees of aHD opening (66°, 68°, and 91°compared with GDP-bound G T , but none as extensively displaced (132°) as aHD in the b 2 AR/Gs crystal structure). Most notably, in all of the three structures, aHD appears to make polar contacts with the Gb 1 subunit, which were found to be crucial to support optimal GDP!GTP exchange rate.…”
Section: Structural Dynamics Of G Protein Activation and Gpcr/g Protementioning
confidence: 99%
“…Notably, this study revealed the putative role of the Gb 1 and the a-helical domain (aHD) of the Ga subunit in the G protein activation process. Whereas aHD is highly flexible (107)(108)(109) and therefore it remains unresolved in other GPCR/G protein cryo-EM structures, Gao et al (108) solved the structures of three Rho/G T complex conformers (at 4.5 Å) that differed in degrees of aHD opening (66°, 68°, and 91°compared with GDP-bound G T , but none as extensively displaced (132°) as aHD in the b 2 AR/Gs crystal structure). Most notably, in all of the three structures, aHD appears to make polar contacts with the Gb 1 subunit, which were found to be crucial to support optimal GDP!GTP exchange rate.…”
Section: Structural Dynamics Of G Protein Activation and Gpcr/g Protementioning
confidence: 99%
“…The new strategies and analysis from Gao et al (6) are different from previous X-ray and cryoEM studies in several ways. First, the authors isolated native bovine rhodopsin and the obligate heterodimer ␤1␥1 complex from photoreceptors, which they paired with a chimeric G␣ T subunit.…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…The structural model by Gao et al (6) provides new information relevant to two outstanding questions: One concerns the large movement of the G␣ helical domain, thought to be necessary for release of GDP from the deeply buried active site. This movement is one of the unique features of the GPCR-G protein complex that was first revealed in spectroscopic experiments of G␣ i activation by rhodopsin (7) and then visualized upon crystallization of ␤ 2 AR-G S (1).…”
Section: G Protein-coupled Receptors (Gpcrs)mentioning
confidence: 99%
“…Rhodopsin is a major component of rod photoreceptors, which are photosensitive, even under extremely weak light conditions (Hargrave and McDowell, 1992 ). The light-activated rhodopsin is the GPCR catalyzing the exchange of GDP for GTP on the heterotrimeric G protein transducin (Gao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%